Optimal life cycle costing in determinig floors materials [electronic resource] - Noorsidi Aizuddin Mat Noor, 1984-; Fakulti Kejuruteraan dan Sains Geoinformasi (2009)
Thesis (Sarjana Sains (Harta Tanah))- Universiti Teknologi Malaysia, 2009